France24_Climate-smart farms in western Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Excerpt from a France24 documentary aired in July 2015. Original video is here: http://www.france24.com/en/20150704-down-to-earth-migrants-climate-change-environment-refugees-kenya-guterres. Excerpt is from minute 12:25